2020
DOI: 10.3390/ijerph17207522
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Fine Particulate Matter (PM4 and PM2.5) during Hand-Made Cookware Operation: Personal, Indoor and Outdoor Levels

Abstract: (1) Exposure of informal artisanal cookware makers to fine particles has not yet been characterized. The aim of this study was to characterize occupational exposure to fine particulate matter (PM4 and PM2.5) levels and fine particulate matter (PM2.5) elemental components; (2) Artisanal cookware makers were recruited from five cookware making sites. Exposure to fine particulate matter was measured for 17 male participants. SidePak personal aerosol monitors (AM520) were used to measure personal exposure to PM4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Hand-made cookware operation involves preparing sand molds for casting, and a smelting process to cast liquid aluminium melted from a collection of scrap metal [ 28 , 29 , 30 ]. Studies conducted among hand-made cookware makers have reported exposure to high levels of metals [ 30 ], and particulate matter [ 31 ]. However, ergonomic risks have not been assessed among these workers.…”
Section: Introductionmentioning
confidence: 99%
“…Hand-made cookware operation involves preparing sand molds for casting, and a smelting process to cast liquid aluminium melted from a collection of scrap metal [ 28 , 29 , 30 ]. Studies conducted among hand-made cookware makers have reported exposure to high levels of metals [ 30 ], and particulate matter [ 31 ]. However, ergonomic risks have not been assessed among these workers.…”
Section: Introductionmentioning
confidence: 99%
“…The source of individual pollutants is challenging; therefore, it is necessary to apply integrated approaches ( i.e. survey and exposure models) ( 155 ).…”
Section: Air Pollution Exposure During Pregnancymentioning
confidence: 99%
“…However, previous studies have shown that these technologies are not as accurate as gravimetric sampling [ 20 ], as they are sensitive to the size distribution, shape, angle, and composition of particles [ 9 ]. Specifically, light-scattering technologies have been found to overestimate the PM 2.5 fraction compared to gravimetric sampling [ [21] , [22] , [23] , [24] ], while underestimating the PM 10 concentration [ 25 ]. In one previous study, the DustTrak DRX underestimated the coarse fractions by approximately 20% in samples collected in a desert environment [ 26 ].…”
Section: Introductionmentioning
confidence: 99%